Changes in thermal resources and limitations for Georgian viticulture. (17th September 2019) - Cola, G.; Mariani, L.; Maghradze, D.; Failla, O.
Abstract: Background and Aims: The growth and development of grapevine is constrained by temperature, affecting the bulk of physiological processes of the plant. The aim of this study was to evaluate the effects of climate change on thermal resources and limitations in the context of Georgia, one of the oldest viticultural areas in the world. Methods and Results: The analysis on daily series of temperature for the time period 1974–2013 for the main viticultural areas of Georgia shows that an abrupt change to warmer temperature occurred in 1994, leading to a decline in low temperature stress and an increase in high temperature stress, associated with more frequent heat waves. The availability of thermal resources for grapevine growth remained unchanged. Conclusions: In Georgia, the shift to warmer temperature did not affect the availability of thermal resources for grapegrowing. Although some attention should be paid to possible damage due to an earlier budburst and increased frost risk. Furthermore, it is important to highlight the strong increase of summer heatwaves with potential negative impacts on grape composition and phenolic maturity, when combined with severe water stress. Significance of the Study: Quantitative studies of the effects of climate change on Georgian viticulture are essential to develop adaptation strategies based on either germplasm (e.g. rootstocks and cultivars) and agronomical practices (e.g. pruning, trellis systems, soil and water management).